Modern War : A Very Short Introduction - English, Richard, 1963- (Oxford, New York Oxford University Press, 2013)
In this accessible and authoritative book, Richard English considers what modern warfare is and what it achieves. Addressing our assumptions about war in the modern period, and drawing upon direct accounts of warfare, he considers its impact on society, culture, economics, as well its future.
Include Illustration, Reference and Index
Keywords: War